Anti-High Mobility Group Box-1 Monoclonal Antibody Attenuates Seizure-Induced Cognitive Decline by Suppressing Neuroinflammation in an Adult Zebrafish Model - Paudel, Yam Nath; Othman, Iekhsan; Shaikh, Mohd. Farooq (Frontiers in Pharmacology, 2021)
Epilepsy is a devastating neurological condition lacking disease-modifying treatment yet has emerged as a global health concern afflicting around 70 million population globally. The precise understanding of the etiopathology of seizure generation is still elusive, however, brain inflammation is considered as a major contributor to epileptogenesis. In this regard, HMGB1 protein being an initiator and crucial contributor of inflammation is known to contribute significantly to seizure generation via activating its principal receptors namely RAGE and TLR4 reflecting a potential therapeutic target. Herein, we evaluated the anti-seizure and memory ameliorating potential of an anti-HMGB1 monoclonal antibody (mAb) (1, 2.5 and 5 mg/kg, I.P.) in a second hit Pentylenetetrazol (PTZ) (80 mg/kg, I.P.) induced seizure model earlier stimulated with Pilocarpine (400 mg/kg, I.P.) in adult zebrafish. Pre-treatment with anti-HMGB1 mAb dose-dependently lowered the second hit PTZ-induced seizure but does not alter the disease progression. Moreover, pre-treatment with three doses of anti-HMGB1 mAb also attenuated the second hit PTZ induced memory impairment in adult zebrafish as evidenced by an increased inflection ration at 3 hr. and 24 hr. trail in T-maze test. Besides, decreased level of GABA and an upregulated Glutamate level was observed in the second hit PTZ induced group, which was modulated by pre-treatment with anti-HMGB1 mAb. Similarly, inflammatory responses occurred during the progression of seizures as evidenced by upregulated mRNA expression of HMGB1, TLR4, NF-κB, TNF-α, CREB-1, and NPY in a second hit PTZ induced group, which was in-turn downregulated upon pre-treatment with anti-HMGB1 mAb reflecting its anti-inflammatory potential. Our findings indicates that anti-HMGB1 mAb attenuates second hit PTZ-induced seizures, ameliorates related memory impairment, and downregulates the seizure induced upregulation of inflammatory markers to possibly protect the zebrafish from the incidence of further seizures through via modulation of neuroinflammatory pathway. . Taken together, our results suggest that HMGB1 inhibition strategy via anti-HMGB1 mAb might represent a potential therapeutic approach for the development of novel therapies that would ultimately overcome the limitation of current anti-epileptic drugs.